Benjamin Smith Barton papers - Barton, Benjamin Smith, 1766-1815.
Photostats of journal (2 volumes), with botanical references, of Barton while on a trip to Virginia. Includes reprint of journal (1938).
Physician and naturalist.
Photostats, in part.
Collection material in English.
Keywords: Plants -- Virginia; Virginia -- Description and travel; Naturalists; Physicians